Asymmetric Information among Stakeholders and Consequences in Vocational Training for Ethnic Minority Youth in Hoa Binh Province - Bui Thanh Minh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The government supports vocational training in order to improve social security for specific population groups, such as the ethnic minority youth. However, there exists information asymmetry among the stakeholders in vocational training, including the ethnic minority youth, local authorities, training institutions, enterprises and state management agencies, leading to adverse selection, moral hazard and principal-agent problem. These problems have negatively impacted the effectiveness of vocational training for ethnic minority youth. Received 19th September 2019; Revised 20th October 2019; Accepted 24th October 2019